Legal Security for Persons with Bipolar Disabilities in Entering Into Agreements - Rihanah Nurdin, Syemmy (Magister Kenotariatan Universitas Pasundan, 2024)
This research aims to examine and understand the certainty of people with bipolar disorder in making agreements. This research is normative legal research because research examines law as a norm related to legal certainty for people with bipolar disabilities in making agreements. The research method used is the normative juridical method, which is a type of research used to examine the application of norms or legal norms enforced in positive law or laws still in force and have the power to bind legal subjects. The results of this research show that there is no legal certainty for people with bipolar disabilities to enter into agreements because there are no strict and adequate regulations that regulate them. Article 433 of the Civil Code is no longer in harmony with Law Number 19 of 2011 concerning the Ratification of the Convention on the Rights of Persons with Disabilities and Law Number 8 of 2016 concerning Persons with Disabilities.